Optimalisasi Perlindungan Ekspresi Budaya Masyarakat Adat di Indonesia - Intan Nevia Cahyana; Ahmad Sabirin (Badan Strategi Kebijakan Hukum, 2023)
There are approximately 33 types of Indonesian culture that have been claimed as belonging to other countries. Among others, there are Reog Ponorogo and Kuda Lumping Dance; both are from East Java. This proves that the regulation of protection related to TCSe in Indonesia has not provided satisfaction to this nation. Based on this phenomenon, the authors are interested in providing solutions through this research. The type of research is juridical-normative. Furthermore, this research intends to define the TCSe protection mechanisms to assist the Indonesian economy given that legal efforts in developing the